The power of survey design : a user's guide for managing surveys, interpreting results, and influencing respondents (Washington, D.C. : World Bank, 2006)
The power of survey design is written for both those who manage surveys and those who use their results, it reveals the multitude of survey design factors that play subtle but crucial roles in the accuracy of survey data and therefore can taint their interpretation, but also offers a guide to the steps involved in administering a survey and convincing potential respondent to participate.
Includes perception questions in the investment climate survey core questionnaire.
Includes bibliographical reference and index
nmn, 07/08/18
Loans
Keywords: Survey designs; Surveys - interpreting results; Social surveys - methodology; Questionaires - methodology